Neovison Vison: Code of Good Practice for Euthanasia in Mink - Korhonen, Hannu T; Huuki, Hanna (SOSIOHUMANIKA, 2013)
ABSTRACT: The new European regulation lays down rules for the killing of animals bred for the production of food, wool, fur, or other products as well as the killing of animals for the purpose of depopulation and for related operators. Regulation emphasizes the meaning of education, competence, and self-monitoring. The operators are obligated to draw up and implement standard operating procedures (SOP). The purpose is to unify the methods and practices used in killing of animals and thereby improve the welfare of animals. SOP needs to set objectives, operating procedures, define the main parameters to be monitored, and guidelines for situations in which an animal is not stunned or killed as expected. The regulation obligates killing device manufacturers to give instructions and recommendations, which are to be taken in to account when drawing up SOP. The killing device must be maintained and checked according to the manufacturersâ instructions by persons, specifically trained for this purpose on a regular basis. The new regulation allows the mink to be euthanized with carbon monoxide (CO), carbon dioxide (CO2), electricity, shooting, and passing through the bolt gun; and the emergency killing of animals weighting less than 5 kg with a blow in the head. Killing will be monitored by observing the animals and monitoring the key parameters affecting the efficiency of euthanasia. These are: concentration, exposure time, temperature, and sufficient filtration. Upon request, SOP, records, and other documents must be given to the competent authority.KEY WORD: Killing methods, gas euthanasia, fur farming, good practice, standard operating procedures, and farmed mink.Â RESUME: Makalah ini berjudul âNeovisonVison: Pedoman Praktek yang Baik untuk Euthanasia dalam Cerpelaiâ. Peraturan Eropa baru menerapkan ketentuan untuk membunuh jenis binatang untuk produksi makanan, wol, bulu, atau produk lain dan juga membunuh binatang untuk tujuan pengurangan populasi dan pelaksana yang terkait. Peraturan menekankan arti pendidikan, kompetensi, dan pengawasan diri. Para pelaksana diwajibkan untuk mempersiapkan dan mengimplementasikan prosedur operasional standar (POS). Tujuannya adalah untuk menyatukan metode dan praktek yang digunakan dalam membunuh binatang dan dengan demikian meningkatkan kesejahteraan binatang. POS perlu menentukan tujuan, prosedur pengoperasian, menentukan parameter utama yang akan diawasi, dan pedoman-pedoman untuk situasi-situasi dimana binatang tidak dibius atau dibunuh seperti yang diharapkan. Peraturan mewajibkan produsen alat pembunuh untuk memberikan instruksi/petunjuk dan rekomendasi, yang akan dipertimbangkan ketika mempersiapkan POS. Alat pembunuh harus dipelihara dan diperiksa menurut instruksi produsen oleh orang-orang, khususnya yang terlatih untuk tujuan ini. Peraturan baru mengizinkan cerpelai dibunuh dengan karbon monoksida (CO), karbon dioksida (CO2), listrik, tembakan, dan menembakan senjata api; serta pembunuhan darurat binatang yang memiliki berat kurang dari 5 kg dengan tembakan di kepala. Pembunuhan akan diawasi dengan mengamati binatang dan mengamati parameter utama yang mempengaruhi efisiensi pembiusan. Parameter tersebut adalah konsentrasi, waktu pencahayaan, suhu, dan filtrasi yang cukup. Atas permintaan, POS, catatan, dan dokumen lainnya harus diberikan kepada pihak berwenang yang kompeten.KATA KUNCI: Metode pembunuhan, pembiusan gas, peternakan bulu, praktek yang baik, prosedur operasiona standar, dan cerpelai yang diternakan.Â About the Author: Prof. Dr. Hannu T. Korhonen and Dr. Hanna Huuki are Researchers at the MTT Agrifood Research Finland, Animal Production Research, SilmÃ¤jÃ¤rventie 2 69100 Kannus, Finland. For academic purposes, they can be contacted via e-mail at: hannu.t.korhonen@mtt.fi How to cite this article? Korhonen, Hannu T. & Hanna Huuki. (2013). âNeovison Vison: Code of Good Practice for Euthanasia in Minkâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.1 [Mei], pp.69-76. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112.Chronicle of article: Accepted (March 9, 2013); Revised (April 10, 2013); and Published (May 20, 2013). Â  Â